Application of advanced X-ray methods in life sciences - Sayers, Zehra; Avşar, Bihter; Cholak, Ersoy; Karmous, Ines (Biochimica et biophysica acta. General subjects, 2017)
Synchrotron radiation (SR) sources provide diverse X-ray methods for the investigation of structure–function relationships in biological macromolecules. Recent developments in SR sources and in the X-ray tools they offer for life sciences are reviewed. Specifically, advances in macromolecular crystallography, small angle X-ray solution scattering, X-ray absorption and fluorescence spectroscopy, and imaging are discussed with examples. SR sources offer a range of X-ray techniques that can be used in a complementary fashion in studies of biological systems at a wide range of resolutions from atomic to cellular scale. Emerging applications of X-ray techniques include the characterization of disordered proteins, noncrystalline and nonequilibrium systems, elemental imaging of tissues, cells and organs, and detection of time-resolved changes in molecular structures. X-ray techniques are in the center of hybrid approaches that are used to gain insight into complex problems relating to biomolecular mechanisms, disease and possible therapeutic solutions. This article is part of a Special Issue entitled “Science for Life”. Guest Editors: Dr. Austen Angell, Dr. Salvatore Magazù and Dr. Federica Migliardo. •3rd generation synchrotron radiation (SR) facilities are powerful X-ray sources.•X-ray diffraction, scattering and absorption have become routine tools in biology.•New X-ray applications are disordered proteins and molecular kinetics.•New hybrid methods require advanced data management and analysis tools.